Prognostic performance of serial in‐hospital measurements of copeptin and multiple novel biomarkers among patients with worsening heart failure: results from the MOLITOR study. (24th February 2018) - Düngen, Hans‐Dirk; Tscholl, Verena; Obradovic, Danilo; Radenovic, Sara; Matic, Dragan; Musial Bright, Lindy; Tahirovic, Elvis; Marx, Almuth; Inkrot, Simone; Hashemi, Djawid; Veskovic, Jovan; Apostolovic, Svetlana; et al.
Abstract: Aims: In heart failure, various biomarkers are established for diagnosis and risk stratification; however, little is known about the relevance of serial measurements during an episode worsening heart failure (WHF). This study sought to investigate the trajectory of natriuretic peptides and multiple novel biomarkers during hospitalization for WHF and to determine the best time point to predict outcome. Methods and results: MOLITOR (Impact of Therapy Optimisation on the Level of Biomarkers in Patients with Acute and Decompensated Chronic Heart Failure) was an eight‐centre prospective study of 164 patients hospitalized with a primary diagnosis of WHF. C‐terminal fragment of pre‐pro‐vasopressin (copeptin), N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP), mid‐regional pro‐atrial natriuretic peptide (MR‐proANP), mid‐regional pro‐adrenomedullin (MR‐proADM), and C‐terminal pro‐endothelin‐1 (CT‐proET1) were measured on admission, after 24, 48, and 72 h, and every 72 h thereafter, at discharge and follow‐up visits. Their performance to predict all‐cause mortality and rehospitalization at 90 days was compared. All biomarkers decreased during recompensation ( P  < 0.05) except MR‐proADM. Copeptin at admission was the best predictor of 90 day mortality or rehospitalization ( χ 2  = 16.63, C ‐index = 0.724, P  < 0.001), followed by NT‐proBNP ( χ 2  = 10.53, C ‐index = 0.646, P  = 0.001), MR‐proADM ( χ 2  = 9.29, C ‐index = 0.686, P  = 0.002), MR‐proANP ( χ 2  = 8.75, C ‐index = 0.631, P  = 0.003), and CT‐proET1 ( χ 2  = 6.60, C ‐index = 0.64, P  = 0.010). Re‐measurement of copeptin at 72 h and of NT‐proBNP at 48 h increased prognostic value ( χ 2  = 23.48, C ‐index = 0.718, P  = 0.00001; χ 2  = 14.23, C ‐index = 0.650, P  = 0.00081, respectively). Conclusions: This largest sample of serial measurements of multiple biomarkers in WHF found copeptin at admission with re‐measurement at 72 h to be the best predictor of 90 day mortality and rehospitalization.